2015
DOI: 10.2146/sp150016
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of unfractionated heparin protocols using antifactor Xa monitoring or activated partial thrombin time monitoring

Abstract: The antifactor Xa assay should be used to monitor UFH versus aPTT due to less variability in measurements, the absence of a need for calibration with new reagents/coagulometers, quicker attainment of therapeutic levels, fewer dose adjustments, and similar bleeding rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 15 publications
2
28
0
Order By: Relevance
“…Studies have suggested that monitoring UFH infusions with anti-Xa levels compared to aPTT is superior in maintaining values within goal range. 21,22 However, therapeutic dosing of UFH with regards to safety and efficacy has been guided by aPTT, not anti-Xa levels in clinical trials, mostly acute coronary syndrome. This study did not assess the difference in bleeding events and the type of monitoring used (aPTT or anti-Xa).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have suggested that monitoring UFH infusions with anti-Xa levels compared to aPTT is superior in maintaining values within goal range. 21,22 However, therapeutic dosing of UFH with regards to safety and efficacy has been guided by aPTT, not anti-Xa levels in clinical trials, mostly acute coronary syndrome. This study did not assess the difference in bleeding events and the type of monitoring used (aPTT or anti-Xa).…”
Section: Resultsmentioning
confidence: 99%
“…Differences in physician, pharmacy and nursing practice can affect the degree of UFH infusion prescribing, dosing, titration, and monitoring. Studies have suggested that monitoring UFH infusions with anti‐Xa levels compared to aPTT is superior in maintaining values within goal range . However, therapeutic dosing of UFH with regards to safety and efficacy has been guided by aPTT, not anti‐Xa levels in clinical trials, mostly acute coronary syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported the discordance of the APTT with anti-Xa values in monitoring heparin (15)(16)(17)(18)(19) and many studies have focused on one particular age group, either infants (18) or adults (16;17;19). One study demonstrated that nearly 57% of patients in the anti-Xa group were in range within 6 hours of initiation of UFH versus 27% in the APTT group (p = 0.001) (20). Patients in the anti-Xa group had an average of 1.00 dosage adjustments per subject compared to 1.71 in the APTT group within the first 24 hours (p = 0.003) (20).…”
Section: Discussionmentioning
confidence: 99%
“…One study demonstrated that nearly 57% of patients in the anti-Xa group were in range within 6 hours of initiation of UFH versus 27% in the APTT group (p = 0.001) (20). Patients in the anti-Xa group had an average of 1.00 dosage adjustments per subject compared to 1.71 in the APTT group within the first 24 hours (p = 0.003) (20). (40%) concordance of APTT and anti-Xa values (19).…”
Section: Discussionmentioning
confidence: 99%
“…Fewer dose adjustments and repeat tests are required, which may also result in lower cost. 32,[51][52][53][54][55] While these studies found chromogenic anti-Xa assays better for achieving laboratory end points, data regarding relevant clinical outcomes are more limited. In a retrospective, observational cohort study, 51 the rate of venous thromboembolism or bleeding-related death was 2% in patients receiving unfractionated heparin therapy monitored by anti-Xa assay and 6% in patients monitored by aPTT (P = .62).…”
Section: ■ Clinical Applicability Of the Anti-xa Assaymentioning
confidence: 99%